Bringing power back in: A review of the literature on the role of business in welfare state politics - Thomas Paster (Max Planck Institute for the Study of Societies, 2015)
What is the impact of business interest groups on the formulation of public social policies? This paper reviews the literature in political science, history, and sociology on this question. It identifies two strands: one analyzes the political power and influence of business, the other the preferences and interests of business. Since the 1990s, researchers have shifted their attention from questions of power to questions of preferences. While this shift has produced important insights into the sources of the policy preferences of business, it came with a neglect of issues of power. This paper takes a first step towards re-integrating a power-analytical perspective into the study of the role of business in welfare state politics. It shows how a focus on variation in business power can help to explain both why business interest groups accepted social protection during some periods in the past and why they have become increasingly assertive and averse to social policies since the 1970s. – – Wie beeinflussen Unternehmensverbände die Gestaltung staatlicher Sozialpolitik? Dieses Papier bietet einen Überblick über die politikwissenschaftliche, geschichtswissenschaftliche und soziologische Forschungsliteratur zu diesem Themenfeld. Es identifiziert zwei Forschungsstränge: Einer befasst sich mit politischer Macht und Einflussnahme von Unternehmen und der andere mit deren sozialpolitischen Interessen und Präferenzen. Seit den 1990er-Jahren verlagert sich der Schwerpunkt der Forschung vom ersten zum zweiten Strang. Diese Verlagerung brachte wichtige neue Einsichten in die sozialpolitischen Präferenzen von Unternehmen, führte jedoch zu einer Vernachlässigung von Fragen nach Ursachen und Stärke des politischen Einflusses von Unternehmen. Der Bericht versucht, die machtanalytische Perspektive in die Untersuchung der Ausgangsfrage - wie Unternehmensinteressen Sozialpolitik beeinflussen - zu reintegrieren. Durch diesen Blick auf die verschiedenen Ausprägungen politischen Einflusses kann erklärt werden, warum Unternehmensverbände sozialpolitische Reformen in bestimmten Perioden akzeptierten, jedoch seit den 1970er-Jahren staatlicher Sozialpolitik zunehmend kritisch gegenüberstehen.
Keywords: 300